PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK), DAN DANA BAGI HASIL (DBH) TERHADAP BELANJA DAERAH DI KABUPATEN JOMBANG PERIODE 2005–2024 - Kharisma Tri Buana Dewi; Renny Oktafia (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2026)
This study analyzes the influence of Local Own-Source Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on the Regional Expenditure of Jombang Regency during 2005–2024 within the context of fiscal decentralization. The urgency of this research arises from the region's high dependence on central government transfers and the need to enhance regional fiscal capacity independently. The data used are secondary time series data obtained from the Ministry of Finance and regional government financial documents. The analysis was conducted using multiple linear regression after passing classical assumption tests to ensure model validity. The results indicate that PAD has a positive but insignificant effect on Regional Expenditure, suggesting that its contribution to expenditure capacity remains limited. DAU has a positive and significant effect, confirming the dominance of central government transfers on regional spending. DAK also has a positive but insignificant effect, consistent with its predetermined usage. DBH has a positive and significant effect, providing additional fiscal space for the local government. Simultaneously, all four variables significantly influence Regional Expenditure, illustrating that Jombang Regency’s fiscal structure is shaped by a combination of own-source revenue and transfer funds. These findings also reinforce the flypaper effect phenomenon, where regional expenditure is more influenced by transfer funds than PAD. This study is expected to provide insights for local governments to enhance fiscal independence and optimize budget management.